2000
DOI: 10.1152/jn.2000.83.3.1283
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in the Primate Superior Colliculus Coding for Arm Movements in Gaze-Related Coordinates

Abstract: In the intermediate and deep layers of the superior colliculus (SC), a well-established oculomotor structure, a substantial population of cells is involved in the control of arm movements. To examine the reference frame of these neurons, we recorded in two rhesus monkeys (Macaca mulatta) the discharges of 331 neurons in the SC and the underlying mesencephalic reticular formation (MRF) while monkeys reached to the same target location during different gaze orientations. For 65 reach-related cells with sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(149 citation statements)
references
References 56 publications
10
137
1
1
Order By: Relevance
“…Strong correlations between electromyographic activity of arm muscles and neuronal activity of a collicular "reach cell" have been found for proximal muscles. However, the correlation obtained for distal muscles, such as the flexor digitorum superficialis, was much less frequent and weak (18), confirming previous findings linking the superior colliculus to orienting movements of the eyes, head and arms (e.g., 17,21). So, if collicular mechanisms are, in fact, mediating the facilitation in the GAP paradigm, the GAP effect for key-press responses should be minimal or even nonexistent.…”
Section: Discussionsupporting
confidence: 83%
“…Strong correlations between electromyographic activity of arm muscles and neuronal activity of a collicular "reach cell" have been found for proximal muscles. However, the correlation obtained for distal muscles, such as the flexor digitorum superficialis, was much less frequent and weak (18), confirming previous findings linking the superior colliculus to orienting movements of the eyes, head and arms (e.g., 17,21). So, if collicular mechanisms are, in fact, mediating the facilitation in the GAP paradigm, the GAP effect for key-press responses should be minimal or even nonexistent.…”
Section: Discussionsupporting
confidence: 83%
“…Although Li and Lin (2002) and Kingstone and Pratt (1999) found more IOR for keypress-eye than for keypress-alone movements, this was not the case for the conjoined and independent pointing responses (hand and mouse) examined by Khatoon et al (2002). This separation on response types may occur because pointing responses require considerable SC involvement (Stuphorn, Bauswein, & Hoffmann, 2000;Werner, Dannenberg, & Hoffmann, 1997), with the inhibition in the SC essentially at ceiling and leaving little room for any additional inhibition associated with the saccade responses. Presumably, keypress responses-which have much lower spatial requirements and therefore require less SC activation-are well away from any maximal level of inhibition in the SC and are thus more likely to piggyback on saccadic IOR.…”
mentioning
confidence: 90%
“…At a neural level, it has been suggested that timing between eyes and upper limb in pointing tasks relies on signal interchange and probably resides in the superior colliculus where signals of the oculomotor and manual control systems converge (Reyes-Puerta et al 2010;Stuphorn et al 2000;Werner et al 1997). Indeed, neuronal activity of the superior colliculus, an area classically linked with gaze fixation (Munoz and Wurtz 1993a, b), is known to be partly modulated by the arm movements involved in reaching (Reyes-Puerta et al 2010;Stuphorn et al 1999;Stuphorn et al 2000;Werner et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, neuronal activity of the superior colliculus, an area classically linked with gaze fixation (Munoz and Wurtz 1993a, b), is known to be partly modulated by the arm movements involved in reaching (Reyes-Puerta et al 2010;Stuphorn et al 1999;Stuphorn et al 2000;Werner et al 1997). In this way, arm movement and the correlated 'reach neurons' can facilitate or inhibit gaze shifts by providing excitatory or inhibitory input to saccadic build-up neurons (Lünenburger et al 2000).…”
Section: Discussionmentioning
confidence: 99%